2011
DOI: 10.1172/jci57456
|View full text |Cite
|
Sign up to set email alerts
|

GATA3 controls Foxp3+ regulatory T cell fate during inflammation in mice

Abstract: Tregs not only keep immune responses to autoantigens in check, but also restrain those directed toward pathogens and the commensal microbiota. Control of peripheral immune homeostasis by Tregs relies on their capacity to accumulate at inflamed sites and appropriately adapt to their local environment. To date, the factors involved in the control of these aspects of Treg physiology remain poorly understood. Here, we show that the canonical Th2 transcription factor GATA3 is selectively expressed in Tregs residing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

29
493
3
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 475 publications
(526 citation statements)
references
References 86 publications
(122 reference statements)
29
493
3
1
Order By: Relevance
“…It was interesting to see that the different expression patterns of CCR6 and CXCR3 showed orthogonal patterns of expression in RORC, TBX21, and GATA3. In addition, there was a similar pattern of expression between GATA3 and FOXP3, consistent with the role of GATA3 on FOXP3 expression (23,24).…”
Section: Gene Expression Profiling Identifies Five Major Subgroups Ofsupporting
confidence: 74%
“…It was interesting to see that the different expression patterns of CCR6 and CXCR3 showed orthogonal patterns of expression in RORC, TBX21, and GATA3. In addition, there was a similar pattern of expression between GATA3 and FOXP3, consistent with the role of GATA3 on FOXP3 expression (23,24).…”
Section: Gene Expression Profiling Identifies Five Major Subgroups Ofsupporting
confidence: 74%
“…12 Similarly, the Th2-associated transcription factor GATA3 was found to play an important role for Treg function, as it was shown that GATA3-deficient Tregs display profound defects in peripheral homeostasis and suppressive function. 13,14 In addition, Treg-specific deletion of the transcription factors IRF4 (interferon regulatory factor 4) or STAT3 (signal transducer and activator of transcription 3) resulted in an impaired regulation of Th2-and Th17-dominated immune responses, respectively. 15,16 Recently, a population of germinal center-resident Tregs, termed follicular regulatory T cells, was identified.…”
Section: Introductionmentioning
confidence: 99%
“…The transcription factor Foxp3 plays a crucial role in immune homeostasis and T reg development (34)(35)(36), as demonstrated by the dramatic autoimmune phenotype of the Foxp3 forkhead domain-deficient Scurfy mouse (37), and autoimmune disease in humans bearing Foxp3 mutations known as immunodysregulation polyendocrinopathy enteropathy X-linked syndrome. Foxp3 expression itself is regulated by cooperative activation of multiple transcription factors by cytokine receptors, including the TGF-β receptor (26,(38)(39)(40)(41). Specifically, TGF-β receptor binding causes the transcription factors Smad3 and nuclear factor of activated T cells (NFAT) to promote Foxp3 expression through histone acetylation at one of two known enhancer elements (26).…”
mentioning
confidence: 99%